2016
DOI: 10.1021/acssuschemeng.5b01460
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of TiO2/CuS Core/Shell and Composite Nanostructures for Efficient Visible Light Photocatalysis

Abstract: An enduring impediment in the photocatalysis domain is the rapid recombination of photoinduced charge carriers. One viable strategy to realize efficient separation of photoinduced charge carriers is to design core/shell nanostructures. In this context, our work explains the substantial separation of photocarriers and enhanced light harvesting in TiO 2 nanostructures following the realization of core/shell geometry with CuS. We demonstrate the design of the TiO 2 /CuS core/shell nanostructures, utilizing a surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(89 citation statements)
references
References 46 publications
(72 reference statements)
3
81
0
Order By: Relevance
“…CdS and CdSe nanoparticle deposited on ordered TiO 2 nanotubes [20] were found to efficiently degrade methylene orange dye (up to 95%) within 120 min of visible light irradiation. Ninety percent MB dye degradation was achieved in the presence of visible light by TiO 2 /CuS composite nanostructure, synthesized via surface functionalization route [21]. In all the above-mentioned reports, there was a requirement of integrating TiO 2 with semiconductors into a single nanoscale heterostructure, which in itself requires extensive synthesis.…”
Section: Photocatalytic Degradation Of Mb Dyementioning
confidence: 99%
“…CdS and CdSe nanoparticle deposited on ordered TiO 2 nanotubes [20] were found to efficiently degrade methylene orange dye (up to 95%) within 120 min of visible light irradiation. Ninety percent MB dye degradation was achieved in the presence of visible light by TiO 2 /CuS composite nanostructure, synthesized via surface functionalization route [21]. In all the above-mentioned reports, there was a requirement of integrating TiO 2 with semiconductors into a single nanoscale heterostructure, which in itself requires extensive synthesis.…”
Section: Photocatalytic Degradation Of Mb Dyementioning
confidence: 99%
“…Photocatalysis based on TiO 2 is particularly attractive because of its wide availability, low cost, and non‐toxicity . Recently, TiO 2 and its composites have been extensively utilised as photocatalysts for the removal of dyes from wastewater .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Photocatalysis based on TiO 2 is particularly attractive because of its wide availability, low cost, and non-toxicity. [18][19][20][21] Recently, TiO 2 and its composites have been extensively utilised as photocatalysts for the removal of dyes from wastewater. 22 For example, Zhang et al demonstrated a UV-visible light photocatalysis process for the degradation of azo dyes using TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For BiOCl, almost negligible peaks were detected whereas a gradual increase in peak intensity was observed for NPB20 composite as the visible light irradiation time increases from 0 to 60 min ( Figure 14). This indicates that the fluorescence is caused by chemical reactions of terephthalic acid with ȮH formed on the NPB20/water interface via photocatalytic reactions [65]. [60,66].…”
Section: Mechanistic Outlooks For Photocatalytic Degradation Of Mo Unmentioning
confidence: 99%